Gambaran Pelayanan Promotif Kesehatan Fisioterapi di Puskesmas Wilayah Kabupaten Klaten - Astuti, Dwi Nur; Triyana, Triyana (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Community Health Centers are first-level health service facilities that play an important role in organizing public health efforts and first-level individual health efforts, by prioritizing promotive and preventive efforts, to achieve the highest level of public health in their working areas. Physiotherapy is one of the innovative services in Community Health Centers by prioritizing promotive and preventive services without neglecting curative and rehabilitative efforts in accordance with Permenkes No. 65 of 2015. Therefore, the implementation of ideal promotive and preventive physiotherapy services in Community Health Centers is needed to achieve the goals of health transformation, the pillar of primary service transformation, namely strengthening promotive preventive activities to create more healthy people, improving health screening and increasing the capacity of primary services. Objectives: This study aims to analyze to determine the description of promotive physiotherapy services in the Klaten district. Methods: This study uses a qualitative research methodology with a phenomenological approach to see an in-depth description of promotive physiotherapy services in Community Health Centers in the Klaten area. Results: The results obtained showed that 29 physiotherapists at the Health Center had provided promotive services in the form of counseling, screening and consultation to target communities including toddlers, school children, adolescents, the elderly and certain communities. Conclusion: Promotive physiotherapy services at the Klaten Health Center that have been carried out are in the form of counseling, screening and consultation, the promotive form is education related to LBP, OA, early detection of falls, elderly health, and others. Keywords : Physiotherapy, Promotion, Puskesmas